ADAPTING THE "ADDIE" INSTRUCTIONAL DESIGN MODEL IN ONLINE EDUCATION - Dan Alexandru SZABO (Studia Universitatis Babes-Bolyai, 2022)
The instructional design approach should begin with requirements evaluation to evaluate the necessities of the online learning event, such as what the learner should understand and be capable of doing as an outcome of the education or understanding solution and what learners immediately understand and can perform. Instructional designers widely use ADDIE to create modules, models, software, and courses for instruction and learning. It is also used as a design model. It presents a series of repetitive steps to build effective education and training in five phases, giving rise to the acronym: A-D-D-I-E, which stands for analysis, design, development, implementation, and evaluation. Received: 2022 March 05; Revised: 2022 March 25; Accepted: 2022 March 28; Available online: 2022 May 5; Available print: 2022 May 30